Extracorporeal blood purification in patients with liver failure: Considerations for the low-and-middle income countries of Latin America - Villanueva, Vladimir Barrera; Barrera Amorós, Daniel Alejandro; Castillo Echeverria, Eira Ingrid; Budar-Fernández, Luis F.; Salas Nolasco, Omar Israel; Juncos, Luis A.; Rizo-Topete, Lilia (Frontiers in Nephrology, 2023)
Severe liver failure is common in Low-and-Medium Income Countries (LMIC) and is associated with a high morbidity, mortality and represents an important burden to the healthcare system. In its most severe state, liver failure is a medical emergency, that requires supportive care until either the liver recovers or a liver transplant is performed. Frequently the patient requires intensive support until their liver recovers or they receive a liver transplant. Extracorporeal blood purification techniques can be employed as a strategy for bridging to transplantation or recovery. The most common type of extracorporeal support provided to these patients is kidney replacement therapy (KRT), as acute kidney injury is very common in these patients and KRT devices more readily available. However, because most of the substances that the liver clears are lipophilic and albumin-bound, they are not cleared effectively by KRT. Hence, there has been much effort in developing devices that more closely resemble the clearance function of the liver. This article provides a review of various non-biologic extracorporeal liver support devices that can be used to support these patients, and our perspective keeping in mind the needs and unique challenges present in the LMIC of Latin America.